Kedudukan Hakim dalam Proses Pembuktian Perkara Perdata: Tinjauan Kepustakaan atas Doktrin dan Yurisprudensi - Ismaya Rahailia Nasution; Sidi Ahyar Wiraguna (Lembaga Pengembangan Kinerja Dosen, 2025)
The position of judges in the process of proving civil cases occupies a fundamental role in upholding justice and legal certainty within the Indonesian judicial system. This study aims to examine the judge’s position, duties, and authority in the evidentiary process of civil cases through a literature review focusing on doctrines and jurisprudence. Using a normative juridical method with a library research approach, this paper analyzes legal theories, statutory provisions, and judicial precedents that regulate evidentiary procedures in civil law. The findings show that a judge is not merely a passive law enforcer but an active truth-seeker who must interpret and assess evidence based on principles of fairness, propriety, and moral values. The judge’s discretion in evaluating evidence reflects the responsibility to harmonize formal legal norms with the pursuit of substantive justice. Jurisprudence demonstrates that judges play an essential role in shaping evidentiary standards and ensuring that court decisions reflect the ideals of justice and legal certainty. The study concludes that the authority and independence of judges are crucial in realizing a fair trial, as they ensure that decisions are based on verified facts, logical reasoning, and moral responsibility. Strengthening the professionalism and integrity of judges is necessary to guarantee that the evidentiary process in civil proceedings fulfills the principles of equality before the law and promotes justice in society.